Expert fraud investigation : a step-by-step guide - Coenen, Tracy, 1972- (Hoboken, N.J. : John Wiley & Sons, 2009)
This book delivers an excellent primer on the many fraud shemes as well as practical investigative techniques to detect and prevent fraud.
Includes index..
aug 31/05/13
Loans
Keywords: Fraud; Investigations